Proceedings of the 2008 ACM Conference on Computer Supported Cooperative Work 2008
DOI: 10.1145/1460563.1460657
|View full text |Cite
|
Sign up to set email alerts
|

Colour management is a socio-technical problem

Abstract: This paper describes how achieving consistent colour reproduction across different devices is a complicated matter. Although there is a technological infrastructure for managing colour across devices this is very rarely used as intended. This infrastructure has been created by modelling the problem of colour management as a wholly technical one. In this paper we illustrate the importance of understanding the management of colour as a sociotechnical problem, by describing the findings of a multisited ethnograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…For example, data visualization researchers use computer-aided color-coding to represent and interact with their data [11] or to map data along color dimensions to create a pictorial representation [3]. The print industry defines standard color references, such as the PMS Pantone Matching System, according to specific ink formuli or a CMYK mix [22], with corresponding reference guides for various print devices and substrates.…”
Section: Representing and Visualizing Colormentioning
confidence: 99%
“…For example, data visualization researchers use computer-aided color-coding to represent and interact with their data [11] or to map data along color dimensions to create a pictorial representation [3]. The print industry defines standard color references, such as the PMS Pantone Matching System, according to specific ink formuli or a CMYK mix [22], with corresponding reference guides for various print devices and substrates.…”
Section: Representing and Visualizing Colormentioning
confidence: 99%
“…The analysis of Jacucci and Wagner (2007) shows that materiality supports intuitive and simultaneous manipulation, mobilizing our tacit knowledge and enabling participation. Focusing on the work practices of graphics designers, O'Neill et al (2008) ethnographic results revealed that designers build up practical, tangible, visual understandings of colour and suggested such an understanding of colour schemes is not supported by the current technologies. They claimed that current technologies required designers to deal with colour in an abstract manner.…”
Section: Related Work-studying Design Practicesmentioning
confidence: 99%
“…However, as the studies on design practices showed (Jacucci and Wagner 2007;O'Neill et al 2008), work in design studios goes well beyond productivity measures. Designers involve in several experiential and aesthetical processes such as exploring and playing their materials and design artefacts, communicating empathy of their field visits to colleagues and immerse themselves into participatory and role-playing methods, amongst a large set of other activities.…”
Section: Beyond Productivity: Our Approachmentioning
confidence: 99%
“…Even the expertise required to implement ICC‐based colour management is typically challenging for artists and designers who are not experts in colour science and/or digital technology . Lack of CAD expertise in the areas of colour control is still shown to be a barrier to the successful adoption of design technology amongst small entrepreneurial design businesses .…”
Section: Introductionmentioning
confidence: 99%